2011
DOI: 10.1111/j.2042-3306.2011.00428.x
|View full text |Cite|
|
Sign up to set email alerts
|

Is there a statistical correlation between ultrasonographic findings and definitive diagnosis in horses with acute abdominal pain?

Abstract: SummaryReason for performing study: Abdominal ultrasonography has become a part of the diagnostic investigation for the acute abdomen in many equine clinics. There is limited information on the correlation between abnormalities detected on abdominal ultrasonography and the specific category of small intestine (SI) and large intestine (LI) diseases. Objectives: To investigate the relationship between abdominal ultrasonographic findings and disease categories that cause abdominal pain requiring surgery. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 29 publications
2
50
0
18
Order By: Relevance
“…Porém, em concordância com outros autores, destaca-se que como outros procedimentos diagnósticos auxiliares, essa modalidade deve ser aplicada e interpretada respeitando os achados clínicos e os resultados de outros exames, servindo como uma excelente técnica complementar (BECATI et al, 2011;BUSONI et al, 2011).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Porém, em concordância com outros autores, destaca-se que como outros procedimentos diagnósticos auxiliares, essa modalidade deve ser aplicada e interpretada respeitando os achados clínicos e os resultados de outros exames, servindo como uma excelente técnica complementar (BECATI et al, 2011;BUSONI et al, 2011).…”
Section: Discussionunclassified
“…Aliado a isso, uma maior exigência do proprietário quanto a buscas e recursos apropriados para o seu correto diagnóstico e tratamento aumenta a cada dia. Os médicos veterinários especialistas na área enfrentam nos quadros de cólica a necessidade de uma decisão rápida e eficiente quanto à escolha do tratamento clínico ou cirúrgico (BECATI et al, 2011;REEVES et al, 1991).…”
Section: Introductionunclassified
“…It was demonstrated that transabdominal ultrasound examination is helpful part of diagnostic investigation of equine abdomen [2]. Furthermore, combined transabdominal and inguinal ultrasonography is reported as a highly sensitive technique for evaluation of cryptorchid testis.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography is used increasingly to assess the gastrointestinal tract and can add considerably to the clinical database [18,19], particularly in foals [20]. Nevertheless, studies comparing various novel biomarkers in surgical and nonsurgical patients continue to be published.…”
Section: Are There Better Diagnostic Tools To Assess Colic Cases?mentioning
confidence: 98%